A-263 Literacy Acquisition Shaped by Bilingual Education. (17th August 2022) - Florentino, Nicole L; Shelton, Tiffani P; Lebell, Danya S; Caballero, Jocelyn; Bouhali, Florence; Kovelman, Ioulia; Tonkovich, Yuuko Uchikoshi; Hoeft, Fumiko
Abstract: Objective: This study investigates how literacy acquisition is shaped by bilingual education. We hypothesize that learning a phonetic language, like Spanish, will improve performance on phonologically-based tasks in English. Comparatively, we expect learning a different orthographic system, like Cantonese, will improve performance on semantically-based English tasks. Methods: Participants included 107 native English speakers between 7 and 9 years old from San Francisco schools. There were 42 children in general education English programs (GENED), 35 in Spanish (Sp) immersion programs, and 30 in Cantonese (Cn) immersion programs. Students scoring less than 85 on a nonverbal intelligence screener were excluded (KBIT-2 Matrices). Groups' performance in English was compared on phonological (CTOPP-2 Blending Words) and orthographic learning tasks (KABC-II Rebus). Results: One-way ANOVA revealed a significant effect of bilingual education on phonological task performance at the p < .05 level [F(2, 66.4) = 3.52, p = .035]. As predicted, the Spanish-immersion group performed better on the phonological task (Blending Words, p = .035; GENED M = 8.55, Sp M = 10.09, Cn M = 9.03). Performance on the semantic task did not significantly vary among groups [F(2, 67) = 3.11, p = .051]. Conclusions: This suggests that learning a second language may shape literacy acquisition in the primary language. Results indicated that learning Spanish, a phonetic language, was associated with stronger performance on an English phonological task when compared to GENED and Cn immersion. Although the variance between groups on the semantic task was not significant, further research could characterize the impact of different orthography on English acquisition.